Review of Sulfate Removal in Low Concentration Brine Solutions - Paulo Guilherme Freitas Melo; Kátia Cecília de Souza Figueiredo (Sustainable Chemical Engineering, 2024)
Sulfate is a common ion present in natural water bodies at low concentrations and as an effluent in different metallurgical processes. The discharge of sulfate into rivers and water bodies can cause direct and indirect environmental damage. Regulatory agencies have been increasing restrictions on sulfate content limits for discharge, focusing on human equity and environmental protection. A common practice is the precipitation of sulfate with lime, but the remaining solution still contains approximately 1,500 mg L-1 of sulfate, which is not acceptable for disposal or reuse. This work describes the main routes for sulfate removal, such as chemical precipitation, biological degradation, ion exchange, and membrane separation, and discusses the main advantages and issues of each approach. One of the main challenges is scaling up the tests and demonstrating their performance at the industrial level. The subject must be the focus of ongoing research to obtain relevant results, so that conventional technologies can be replaced by more innovative, cost-effective, and efficient methods.